Lesson Learned From the Great Kanto Earthquake to the Kumamoto Earthquake to Improve Crisis Management Process - Preedaananthasuk, Chatree (Thai Journal of East Asian Studies, 2019)
Natural Disasters are regarded as crises caused by the act of nature not by human. It is hard to avoid natural disasters, but we can learn from crisis response how to improve crisis management process. Crisis Management process is not complete if we focus only reactive crisis management process. A crisis may recur if an organization unlearns previous crisis experience Japan is one of the favorite tourist destinations and is also an earthquake-prone country. Great earthquakes in the past destroyed cities and killed many people in Japan, and it provided lesson learned how to improve crisis response. This study applied case studies of earthquakes in Japan from the Great Kanto Earthquake to the Kumamoto Earthquake to illustrate the Framework of Integrated Crisis Management. Research results emphasized on learning process which is one of important parts of Integrated Crisis Management.